The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.4274/tjps.galenos.2018.27146
|View full text |Cite
|
Sign up to set email alerts
|

The Anticancer and Anti-inflammatory Effects of <i>Centaurea solstitialis</i> Extract on Human Cancer Cell Lines

Abstract: Bitkilerden elde edilen doğal ürünler, kanser dahil çeşitli hastalıkların tedavisinde uzun yıllardır kullanılmaktadır. Centaurea solstitialis subsp. solstitialis'in Türk geleneksel tıbbında yeri olduğu bilinmektedir. Bu araştırma, Muğla ilinden toplanan C. solstitialis'in çiçekli kısımlarından elde edilen etanolik özütün in vitro biyolojik etkilerini belirleyen ilk çalışmadır. Gereç ve Yöntemler: Özütün Daudi, A549 ve HeLa kanser hücrelerine ve normal BEAS-2B hücre hattına karşı sitotoksik etkisi MTT (3-(4,5di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Moreover, Que is considered to be a chemopreventive that acts on signal transduction pathways as modulators to prevent, inhibit, or reverse carcinogenesis. By this activity, it shows many activities such as apoptosis, cell migration, differentiation and proliferation, oxidative balance, and inflammation . It also shows antioxidative activity and inhibits enzymes that activate carcinogens …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Que is considered to be a chemopreventive that acts on signal transduction pathways as modulators to prevent, inhibit, or reverse carcinogenesis. By this activity, it shows many activities such as apoptosis, cell migration, differentiation and proliferation, oxidative balance, and inflammation . It also shows antioxidative activity and inhibits enzymes that activate carcinogens …”
Section: Results and Discussionmentioning
confidence: 99%
“…By this activity, it shows many activities such as apoptosis, cell migration, differentiation and proliferation, oxidative balance, and inflammation. 183 It also shows antioxidative activity and inhibits enzymes that activate carcinogens. 184 2.2.1.1.…”
Section: Introductionmentioning
confidence: 99%
“…According to this study, the highest cytotoxic activity was observed in the Hela cell line with an IC50 value of 63.18 µg/mL while the lowest cytotoxic activity was observed in the A549 cell line with an IC50 value of 252.5 µg/mL. However, it was reported that the IC50 value of 75.25 µg/mL was detected in the BEAS2b normal cell line [27]. In a study by Yirtici et al, it was stated that C. fenzlii Reichardt extract had an inhibitory effect on the MCF-7 cell line.…”
Section: Discussionmentioning
confidence: 67%
“…Our results suggested that these extracts have more cytotoxic potentials against MCF-7 and PC-3 cancer cell lines than against HEK293 cell lines, in other words the cancer cell lines used herein were more sensitive to both extracts than HEK293 cell line. In contrast, the IC50 values of the ethanolic extract of the flowering parts of C. solstitialis on HeLa (cervix adenocarcinoma), Daudi (Burkitt's lymphoma, CCL-213), A549 (lung adenocarcinoma) and BEAS-2B (normal bronchial epithelium) human cell lines at 72 h were reported to be 63.18, 69.27, 252.5 and 75.25 μg mL -1 , respectively [7]. Erenler and coauthors [47] stated that, at 500 μg mL -1 , the methanolic extract of stem parts of C. solstitialis L. ssp.…”
Section: Discussionmentioning
confidence: 94%
“…Centaurea L., which is a medicinal genus belonging to the Asteraceae family, is represented with 217 taxa 60% of which are endemic to Turkey [2]. Members of this genus were proposed to have several biological activities such as antioxidant [3,4], antimicrobial [5] and antiproliferative [6,7] effects. Centaurea solstitialis L. (yellow star thistle) which grows all over Turkey is used for herpes infections around the lips, malaria, upset stomachs, common colds, hemorrhoids, peptic ulcer and abdominal pain [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%